Caudate hyperactivation during the processing of happy faces in borderline personality disorder. (10th December 2021) - Lamers, Agnes; Toepper, Max; Fernando, Silvia Carvalho; Schlosser, Nicole; Lenz, Eva; Woermann, Friedrich; Driessen, Martin; Beblo, Thomas
Abstract: Background: Emotion dysfunction and anhedonia are main problems in borderline personality disorder (BPD). In the present functional magnetic resonance imaging (fMRI) study, we investigated neural activation during the processing of happy faces and its correlates with habitual emotion acceptance in patients with BPD. Methods: 22 women with BPD and 26 female healthy controls watched movie clips of happy and neutral faces during fMRI without any instruction of emotion regulation. To associate neural activation with habitual emotion acceptance, we included individual scores of the Emotion Acceptance Questionnaire (EAQ) as a covariate in brain data analysis. Results: All participants showed amygdala, temporal and occipital activation during the processing of happy compared to neutral faces. Compared with healthy controls, patients with BPD showed significantly more activation within the bilateral caudate. We did not find significant correlations with emotion acceptance. Conclusions: Our results indicate caudate hyperactivation in patients with BPD during the processing of happy faces. Although patients reported significantly less emotion acceptance of positive emotions, an association with neural activation was not detectable. Highlights: More detailed description of the experimental procedure. Addition of information from our previous study. Addition of limitations as suggested.